Methods for conducting unit tests in the C++14 standard using the GMOCK library - Strózik, Kamil (Journal of Computer Sciences Institute, 2019)
The article presents one of the problems encountered when using the C ++ 14 standard along with the Google Mock library. Based on the introduced problem, possible solutions were discussed, as well as an improved scheme for the TDD approach was presented.